The Important Role Of Women's Associations in the Path Towards Women's Education in Bohemia - Lucie Zormanova (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The article follows the development of views on girls' education in the Bohemian lands from its humble beginnings dating back to the middle of the 19th century to allowing university studies for women. Research Aim: The aim of the study is to present the importance of women's associations for the development of women's education in the Bohemian lands. The research question was formulated as follows: How has the education of women within women's associations changed during the 19th century to the first decade of the 20th century? Which goals did the individual associations want to achieve with their activities? What was the curriculum of the schools formed by individual associations? Which target groups did the individual associations focus on? To get these questions answered, we compared women's associations which in the second half of the 19th century and the first decade of the 20th century focused on women's education in the Bohemian lands. Method: The study is carried out using historical-pedagogical research, the method of content analysis of documents was used. Normative materials, archival documents and scientific articles were used. Results: The women's associations pursued various goals: supporting girls and women to be able to play their traditional female roles of wives and mothers as best as they can, helping poor girls and middle-class girls to better position themselves in the labour market, preparing girls for university studies. Conclusions: Women's associations played a significant role in the feminist movement. In consequence of the indomitable work of these associations, women are now educated in various fields, and we can see them in non-stereotypical professions.